Implementation of the concept of sustainable development in communes of the Bydgoszcz district - Matusewicz, Janusz; Harłoziński, Kazimierz (Journal of Education, Health and Sport, 2016)
<span style="font-size: 12.0pt; font-family: ’Times New Roman’,’serif’; mso-fareast-font-family: ’DejaVu Sans’; mso-font-kerning: .5pt; mso-ansi-language: EN; mso-fareast-language: HI; mso-bidi-language: HI;" lang="EN">The issue of development concerns sustainable development at local level. An analysis and evaluation of the implementation of the concept of sustainable development was carried out in gminas constituting the Bydgoszcz district.